2021
DOI: 10.3389/fonc.2021.712553
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Dissections for T3T4 Stage Penile Cancer Patients Without Preoperatively Detectable Lymph Node Metastasis Bring More Survival Benefits: A Propensity Matching Analysis

Abstract: Background and AimsThe current guidelines for the treatment of penile cancer patients with clinically non-invasive normal inguinal lymph nodes are still broad, so the purpose of this study is to determine which patients are suitable for lymph node dissection (LND).MethodsHistologically confirmed penile cancer patients (primary site labeled as C60.9-Penis) from 2004 to 2016 in the Surveillance, Epidemiology, and Results database were included in this analysis. Univariate and multivariate Cox regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[24] This was related to the status of lymph nodes in penile cancer, which is a significant predictor of survival, so inguinal lymph node dissection, which is local control and chemotherapy as a systemic control, can increase the duration of survival of penile cancer patients. [23,25,26] In addition, this study also found that patients who received total penectomy surgery had a longer average survival compared to those who underwent partial penectomy or did not have surgery, but this result was not statistically significant. This is different from a study conducted by Kamel et al (2018) which found that patients with partial penectomy had better 3-year survival compared to total penectomy (83% vs 76% respectively), with HR 0.82 (CI95% 0, 64-1.04) but not statistically significant.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 62%
“…[24] This was related to the status of lymph nodes in penile cancer, which is a significant predictor of survival, so inguinal lymph node dissection, which is local control and chemotherapy as a systemic control, can increase the duration of survival of penile cancer patients. [23,25,26] In addition, this study also found that patients who received total penectomy surgery had a longer average survival compared to those who underwent partial penectomy or did not have surgery, but this result was not statistically significant. This is different from a study conducted by Kamel et al (2018) which found that patients with partial penectomy had better 3-year survival compared to total penectomy (83% vs 76% respectively), with HR 0.82 (CI95% 0, 64-1.04) but not statistically significant.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 62%